Immunohistochemical Studies on Galectin Expression in Colectomised Patients with Ulcerative Colitis. (18th January 2016) - Block, Mattias; Mölne, Johan; Leffler, Hakon; Börjesson, Lars; Breimer, Michael E.
Abstract : Introduction . The aetiology and pathogenesis of ulcerative colitis (UC) are essentially unknown. Galectins are carbohydrate-binding lectins involved in a large number of physiological and pathophysiological processes. Little is known about the role of galectins in human UC. In this immunohistochemical exploratory study, both epithelial and inflammatory cell galectin expression were studied in patients with a thoroughly documented clinical history and were correlated with inflammatory activity. Material and Methods . Surgical whole intestinal wall colon specimens from UC patients (n = 22 ) and controls (n = 10 ) were studied. Clinical history, pharmacological treatment, and modified Mayo-score were recorded. Tissue inflammation was graded, and sections were stained with antibodies recognizing galectin-1, galectin-2, galectin-3, and galectin-4. Results . Galectin-1 was undetectable in normal and UC colonic epithelium, while galectin-2, galectin-3, and galectin-4 were strongly expressed. A tendency towards diminished epithelial expression with increased inflammatory grade for galectin-2, galectin-3, and galectin-4 was also found. In the inflammatory cells, a strong expression of galectin-2 and a weak expression of galectin-3 were seen. No clear-cut correlation between epithelial galectin expression and severity of the disease was found. Conclusion . Galectin expression in patients with UC seems to be more dependent on disease focality and individual variation than on degree of tissue inflammation.